Characterizing Ice-wedge Polygon Geomorphology in the Haughton Impact Structure, Devon Island - Hawkswell, Jordan (Scholarship@Western, 2018)
Ice-wedge polygon networks are a common feature in periglacial environments formed through thermal contraction cracking and snowmelt infiltration. Polygons of similar morphology are ubiquitous throughout the mid-latitudes of Mars and are believed to have formed through thermal contraction processes. This study aims to characterize the polygons on Devon Island in the Canadian Arctic and the significant variations in geomorphology they display. The study uses LiDAR data to map, analyse, and compare three sites of polygonal terrain. Variations in polygon morphology such as size and orthogonality are observed in the relatively small study area. The results show that polygon morphologic variations in the High Arctic are linked mostly to substrate, stage of evolution and topographic factors. Insights into the factors that influence specific polygon morphology has implications for previous methods of predicting polygon morphology using factors such as homogeneity, and for variations of polygonal terrain in the mid-latitudes of Mars.